Education Management of Ulama Kader to Prepare Mubalig Competencies - Kusoy Anwarudin; Yosal Iriantara; Wiwik Dyah Aryani (International Journal of Nusantara Islam, 2021)
The success of the Wasathiyah Islamic Clerical Cadre Education is inseparable from the extent to which MUI conducts an analysis of educational needs in the implementation of planning, organizing, implementing, monitoring and evaluating functions, methods, and learning processes as well as any obstacles faced by the West Java MUI during PKU. Based on the results of the research findings, it was revealed that the data on MUI Ulama Cadre Education (PKU) in West Java province contained the mission of "Islam Wasathiyah" to realize the decision of MUNAS IX MUI 2015 in Surabaya which had two main functions, namely; The first is a personal function, namely the graduates of the tafakkuh Fiddin ulama as preacher cadres who have the ability to guide and guide Islamic teachings to society in a directed, moderate, polite and contextual manner. While the second is a structural function, namely graduates have the ability to become the leadership relay for MUI in the future. Ulama Cadre Education (PKU) to prepare the competence of preachers in MUI West Java province with the mission of Islam Wasathiyah is a form of regeneration of preachers. preacher. Approach to non-formal education theory for adults, Education and Training theory (DIKLAT) through the Analysis of Educational Material Needs, Learning Methods and Processes. Descriptive research method with a qualitative approach. Data collection techniques through triangulation, observation, interviews and documentation study. The conclusion of the PKU research results with the mission "Islam Wasathiyah" MUI West Java province has implemented proven management functions in; (1) Analysis of planning needs is characterized by the formulation of a vision, mission, objectives, material structure, focus methods, instructors, facilities, participant requirements, infrastructure, consolidation and outreach, and budget, conducting the opening ceremony, and successfully getting positive responses from various parties; (2) Analysis of the need for an organizational function marked by the composition of the committee, division of tasks, coordination, consolidation and outreach; (3) Analysis of the needs of the implementation function characterized by students, learning schedules, instructor assignments, the learning process, applying varied methods, and material conveyed, carrying out field studies; (4) Analysis of the needs of the monitoring and evaluation function is indicated by routine supervision, establishing rules of order, conducting motivation, having grid questions, carrying out final examinations and field studies, and managing administration; (5) Barriers and constraints analysis; (a) there are some managers who are less active; (b) less than optimal budget, (c) the backgrounds of students are too diverse; (d) the scoring system is still semi-formal. The results of the study showed that the students 'output was described: (1) a description of the students' scores; (2) the substance of all subjects is understood; (3) master the principles of Islamic Wasathiyah mission; (4) mastering contemporary da'wah methods; (5) able to practice management sciences and da'wah methodology. The results of the study show that the outcome, graduates have a positive change in the picture; (1) there is an increase in science and insight is considered useful; (2) changes in interpreting Wasathiyah's Islamic mission description; (3) feel great benefits; (4) changing styles, a more convident attitude in preaching activities; (4) the scope of da'wah services is getting wider; (6) positive support from the community and wider local government. The results showed that the PKU program with the Islamic Wasatiyah mission in the analysis of educational needs both internally and externally had not been explored in depth, it still needed innovation and creativity which had become a commitment as material for further PKU program development. The results of the study show that this success adds to the credibility of the MUI West Java leadership, marked by full support from various groups, especially from the West Java provincial government and district / city governments in West Java. The results showed that PKU had the mission "Islam Wasathiyah" to be implemented in a sustainable manner. The results of the research show that monitoring and evaluation still require innovative, creative and coordinative development so that the competency standards of graduates are achieved. The results of this study have implications for the West Java MUI and competent parties as input and consideration in an effort to improve the analysis of the needs of PKU management functions. to prepare the preaching competency as expected.